Analysis of the Influence of Raw Material Quality, Product Quality, and Price on Purchasing Decisions with Competitive Advantage as an Intervening Variable in Silungkang Restaurant - Sumiarti; Putra, Ramdani Bayu; Fitri, Hasmaynelis (CV. Science Tech Group, 2025)
Business competition in the restaurant sector continues to experience quite rapid development, which means businesspeople have to be careful when making decisions. Therefore, the purpose of this study is to find out and analyze the influence of raw material quality, product quality, and price on purchasing decisions with competitive advantage as an intervening variable in Silungkang Restaurant. The sample of this study is 100 consumers of the Silungkang Restaurant. The model of this research is structural equation modeling (SEM), with an analysis tool using SmartPLS 3. The findings of this study show that raw material quality, product quality, and competitive advantage have a positive and significant influence on purchasing decisions. In addition, it was also found that the quality of raw materials, product quality, and price had a positive and significant effect on competitive advantage. Meanwhile, price has an effect, but significantly, on the purchase decision. For the indirect influence through the competitive advantage variable, it was found that competitive advantage could not play a role in strengthening the influence of price on purchasing decisions. However, indirect influence through competitive advantage variables, a significant influence was found on the quality of raw materials and product quality on purchasing decisions.